Does marginalization status and distance from the hospital impact the timing of pediatric pyeloplasty in a universal access-to-care system - Khondker, Adree; Dhalla, Rahim; Nguyen, David-Dan; Kwong, Jethro C.C.; Lee, Yerin; Wu, Jeremy; Kim, Jin Kyu; Chua, Michael E.; Rickard, Mandy; Lorenzo, Armando J. (Canadian Urological Association Journal, 2025)
INTRODUCTION: Prior research in the U.S. suggests that marginalized populations tend to undergo pyeloplasty earlier, likely reflecting concerns about the challenges of reliable followup care in this population. This study assessed the effect of sociodemographic marginalization and geographic distance on the timing of pyeloplasty in a universal, single-payer healthcare system. METHODS: We performed a single-center, retrospective study on children undergoing pyeloplasty from 2008-2019. We assessed the impact of marginalization indices (with the Ontario Marginalization Index [ON-Marg]) and geographic distance on timing of pyeloplasty, preoperative ultrasound findings, and renogram features. Unadjusted analysis and Cox proportional regression were performed to determine the effect of marginalization and geography on timing of pyeloplasty. RESULTS: Among 503 patients who underwent pyeloplasty, the median age at surgery was 16 months. Median preoperative anteroposterior diameter (APD) was 22 mm, and split renal function on renogram was 43%. There was no significant effect of marginalization indices on age at surgery. Patients living >50 km from the hospital had a later age at surgery than those living <10 km (p=0.04); however, there was no significant difference in preoperative APD or split function by marginalization index or geographic distance. Adjusted analyses revealed no significant associations between ON-Marg variables or geographic distance with age at surgery. CONCLUSIONS: In a universal healthcare system, marginalization status and geographic distance were not associated with the timing of pyeloplasty. These results contrast with literature from other settings and suggest that access to care can mitigate disparities in pediatric urology care.